2006
DOI: 10.1126/science.1135245
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Identifies IL23R as an Inflammatory Bowel Disease Gene

Abstract: The inflammatory bowel diseases Crohn's disease and ulcerative colitis are common, chronic disorders that cause abdominal pain, diarrhea, and gastrointestinal bleeding. To identify genetic factors that might contribute to these disorders, we performed a genome-wide association study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
2,062
12
30

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,727 publications
(2,180 citation statements)
references
References 29 publications
76
2,062
12
30
Order By: Relevance
“…1,2 To date, different genetic studies have shown several genes playing a relevant role in these diseases, including NOD2/CARD15, 3 DGL5, 4 SLC22A4 and SLC22A5, 5,6 TNFSF15, 7,8 NOD1/CARD4 7 and IL23R. 9,10 NOD2/CARD15 is likely to be the major genetic factor contributing to CD. This gene encodes a protein directly involved in the innate immune response to microbial antigens.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To date, different genetic studies have shown several genes playing a relevant role in these diseases, including NOD2/CARD15, 3 DGL5, 4 SLC22A4 and SLC22A5, 5,6 TNFSF15, 7,8 NOD1/CARD4 7 and IL23R. 9,10 NOD2/CARD15 is likely to be the major genetic factor contributing to CD. This gene encodes a protein directly involved in the innate immune response to microbial antigens.…”
Section: Introductionmentioning
confidence: 99%
“…An IL‐12‐driven Th1 response may dominate during the early stages of CD, implying that susceptibility to IL‐12‐mediated modulation is strongly dependent on the stage of the disease,16 although activities that have been attributed to IL‐12 in the past may have been mediated by IL‐23 17. Several studies have now demonstrated an important role for Th17 cells in intestinal inflammation 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…Chez l'homme, une étude d'association pangénomique a en effet identifié le gène il23r (IL-23 receptor), essentiellement exprimé par les lymphocytes Th17 et les ILC3, comme un gène de prédispo-sition aux maladies inflammatoires chroniques de l'intestin [51]. Chez la souris, les ILC3 ont été impliquées dans le développement de colites induites par Helicobacter hepaticus via leur capacité à produire de l'IL-17 et de l'IFN- [23].…”
Section: Les Ilc3unclassified